PENGARUH PRAKTIK KERJA INDUSTRI DAN PENGUASAAN MATA DIKLAT TERHADAP KESIAPAN KERJA SISWA SMK DI KABUPATEN KENDAL - Margunani, Margunani; Nila, Asna (Dinamika Pendidikan, 2012)
The objective of the study was to investigate the influence of industrial work practices and accounting productive mastery toward studentsâ work readiness in 12the Grade students of accounting program vocational schools in Kendal district both simultaneously and partially. The population of the study was accounting students in state and private vocational school in Kendal, they were 368 students. The samples were 192 students chosen by proportional random sampling technique. Data were collected by documentation and questionnaires, then analyzed by descriptive analysis. Furthermore, hypothesis was tested by multiple linear regression analysis. The result showed that industrial work practices and accounting productive mastery influenced simultaneously toward studentsâ work readiness by 56.6%, and partially, the influence of industrial work practices was 45.02% and the influence of accounting productive mastery was only 18.15%.